Structural Properties of Amorphous Vanadium Pentoxide Under Compression - Thu Nhan, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 40 No 2DO - 10.25073/2588-1124/vnumap.4869, 2024)
Structural properties of amorphous vanadium pentoxide (V 2 O 5 ) under compression have been investigated by molecular dynamics simulation. A simulated amorphous V 2 O 5 was composed of basic structural units of type VO 5 , VO 6 at low-pressures and VO 6 , VO 7 at high-pressures. These basic structural units were connected by vertex-, edge- and face- shared links to form a structural network. The random distribution of atoms and void clusters led to a high degree of disorder in V 2 O 5 structure. Under compression, the fraction of average vertex-, edge- and face- shared links increased strongly. The number of void clusters (VCs) and void tubes (VTs) also increased as the large voids are divided into smaller voids. The obtained results demonstrate that the decreasing of cross-section and increasing of length in VTs mainly cause increasing the ion conductivity of amorphous V 2 O 5 .